(untitled) (Bioscience Journal, 2023)
The adsorptive capacity of charcoal from the husk of the brazil nut fruit, called “ouriço” (the hard ball with nuts inside) for the herbicide dichlorophenoxyacetic acid (2,4-D) was evaluated. Activated carbons were produced from the brazil nut in a tubular oven at 800 °C and activated with CO2 or water steam. The specific surface area was determined by the Brunauer, Emmett and Teller (BET) method, demonstrating the mean density of micropores. Analysis of N2 adsorption/desorption isotherms was undertaken and the morphology of activated carbons was visualized by Scanning Microscopy (SEM). The activated carbons were successfully obtained and had a specific surface area of 395 m2.g-1 and 401 m2.g-1 after activation with either CO2 or water steam, respectively. The highest pore mean density occurred with a diameter of 1.17 nm for carbons activated in both atmospheres. The graph of the adsorption/desorption isotherms of N2 showed Type I isotherms, regardless of the activation atmosphere. The SEM analysis showed that, for both activation atmospheres, pore formation occurred in the shape of uniform honeycomb craters. Adsorption kinetics followed the pseudo-second order model, indicating chemisorption. Regardless of the activation atmosphere, the activated carbon from the brazil nut “ouriço”, was highly efficient for 2,4-D adsorption.